SHP-1-dependent macrophage differentiation exacerbates virus-induced myositis - Watson, Neva B. (J Immunol, 2015)
Virus-induced myositis is an emerging global affliction that remains poorly characterized with few treatment options. Moreover, muscle-tropic viruses often spread to the central nervous system causing dramatically increased morbidity. Therefore, there is an urgent need to explore genetic factors involved in this class of human disease. This report investigates critical innate immune pathways affecting murine virus-induced myositis. Of particular importance, the key immune regulator SHP-1, which normally suppresses macrophage-mediated inflammation, is a major factor in promoting clinical disease in muscle. We show that Theiler’s murine encephalomyelitis virus infection of skeletal myofibers induces inflammation and subsequent dystrophic calcification with loss of ambulation in wild type mice. Surprisingly, although similar extensive myofiber infection and inflammation is observed in SHP-1-deficient (SHP-1(−/−)) mice, these mice neither accumulate dead calcified myofibers nor lose ambulation. Macrophages were the predominant effector cells infiltrating WT and SHP-1(−/−) muscle, and an increased infiltration of immature monocytes/macrophages correlated with absence of clinical disease in SHP-1(−/−) mice, while mature M1-like macrophages corresponded with increased myofiber degeneration in WT mice. Furthermore, blocking SHP-1 activation in WT macrophages blocked virus-induced myofiber degeneration, and pharmacologic ablation of macrophages inhibited muscle calcification in TMEV-infected WT animals. These data suggest that following TMEV infection of muscle, SHP-1 promotes M1 differentiation of infiltrating macrophages, and these inflammatory macrophages are likely involved in damaging muscle fibers. These findings reveal a pathological role for SHP-1 in promoting inflammatory macrophage differentiation and myofiber damage in virus-infected skeletal muscle, thus identifying SHP-1 and M1 macrophages as essential mediators of virus-induced myopathy.